I «volti del dissenso». Il contributo di Kenneth Keniston all’analisi delle culture giovanili - Merico, Maurizio (SocietàMutamentoPolitica, 2017)
The paper explores and analyzes Kenneth Keniston’s researches on the forms of dissent that engaged the US youth between the late 1950s and early 1970s. The resulting review allows to outline, through the continuum between alienation and commitment, the complex interweaving among the processes of social and political change, the biographical dimension and the psychosocial development on which Keniston develops his analysis of the «faces of dissent». The manifold suggestions, until the proposal of identifying the typical features of a «postmodern youth», and the innovative contribution that the analysis developed by Keniston offered, and continues to offer, to the psychological, anthropological and sociological debate on youth and youth cultures are thus highlighted.